Assessment of chimpanzee adenovirus serotype 63 neutralizing antibodies prior to evaluation of a candidate malaria vaccine regimen based on viral vectors. - Nébié, I; Edwards, N; Tiono, AB; Ewer, K; Sanou, G; Soulama, I; Sanon, S; Diarra, A; Yaro, J; Kangoye, D; Imoukhuede, E; Hill, A; et al. (2014)
Prior to a chimpanzee adenovirus-based (ChAd63) malarial vaccine trial, sera were collected to assess ChAd63-specific neutralizing antibody titers in Banfora (Burkina Faso). The low neutralizing antibody titers reported in both adults and children (median titers, 139.1 and 35.0, respectively) are encouraging for the potential use of ChAd63 as a malarial vaccine vector.